Thermoplastic elastomer composite filaments for strain sensing applications extruded with a fused deposition modelling 3D printer. (23rd July 2020) - Georgopoulou, Antonia; Sebastian, Tutu; Clemens, Frank
Abstract: The use of thermoplastic elastomers with conductive fillers enables one to produce strain sensors in a variety of shapes and forms using thermoplastic processing routes. However, some methods of thermoplastic processing are costly and require long production times. Filament printing, an additive manufacturing route that still exhibits a high annual growth rate, is a cost- and time-efficient method of additive processing. In this study a commercial conductive thermoplastic polyurethane (TPU) based fused deposition modelling (FDM) filament and a styrenic block copolymer (TPS) compound were extruded through two different FDM-based nozzle sizes, using an FDM 3D printer. The TPU material could only be extruded through a 0.5 mm orifice; using a lower nozzle diameter resulted in a non-elastic brittle filament. For the TPS material it was possible to produce filaments with diameters of 0.3 mm and 0.5 mm. In all dynamic tests, the extruded commercial piezoresistive TPU filament either showed plastic deformation at higher elongation, which resulted in resistance uncertainty at low strain, or a secondary peak in the resistivity measurement. For the TPS material, mainly the relaxation of the material resulted in lagging of the resistive value at low strain, because of the buckling of the fiber. Using combined dynamic and static measurements, a reproducible signal could be achieved with the TPS-based material, while the TPU-based material could not be used as a sensor in this area of strains.